Dividend Taxation and Firm Performance with Heterogeneous Payout Responses - Katarzyna Bilicka; Irem Güçeri; Evangelos Koumanakos; Katarzyna Anna Bilicka; Irem Guceri (Center for Economic Studies and ifo Institute (CESifo), 2022)
We analyze the short and long-run performance of firms that were differentially affected by a new tax on dividends in the lead-up to the Global Financial Crisis. We use exogenous policy variation for firms with different legal statuses and financial year-end dates to causally identify the policy impact. Consistent with intertemporal tax arbitrage, immediately-affected firms significantly reduce payouts. At a time of severe liquidity shortage, the average firm uses the undistributed cash to pay back debt. In the long run, the allocation of undistributed cash to investment, retained earnings, and debt repayment predicts growth and the likelihood of bankruptcy.
Keywords: H32; H25; G32; G11; 330; dividend tax; firm survival; investment; intertemporal tax arbitrage